Preparation of a New Hydroxymidine, N-Hydroxy-N-o-Tolyl-N´ - (2-Methyl)-Phenyl Benzamidine Hydrochloride - Mishra, Alok; H. Mohabey, Miss (Asian Journal of Chemistry, 2010)
N-Hydroxy-N-o-tolyl-N´-(2-methyl) phenyl benzamidine hydrochloride was prepared by the condensation of equimolar amounts of N-o-tolyl-hydroxylamine and o-tolyl-benzimidoyl chloride in ether medium at 0-5ºC. The resulting white crystals were filtered, washed with ether and recrystallised from minimum volume of absolute ethanol.